2020
DOI: 10.1109/tpwrd.2019.2896490
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proximity Effects on Sheath Losses in Trefoil Cable Arrangements

Abstract: Induced losses are a significant part of the total losses generated in HVAC cables. Presently, IEC 60287-1-1 is used to calculate the ratio of induced loss in a cable's metal sheath to its conductor loss (λ1), assuming uniform current density in both conductors and sheaths. Although this assumption is reasonable for smaller cables, it is questionable for larger cables in close proximity, such as three-core (3C) export cables in Offshore Wind Farm (OWF) projects. The effects of this non-uniform current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…It is observed how the analytical approach underestimates the sheath losses, with differences generally greater than 10 %. This is in good agreement with [1], [15], where it is suggested that 𝑃𝑃 𝑠𝑠 𝑒𝑒𝑐𝑐 may be proportional to circulating losses, especially in larger cables, so 𝜆𝜆′′ 1 should not be neglected. If so, better results are obtained (Fig.…”
Section: A Unarmored Cablessupporting
confidence: 88%
“…It is observed how the analytical approach underestimates the sheath losses, with differences generally greater than 10 %. This is in good agreement with [1], [15], where it is suggested that 𝑃𝑃 𝑠𝑠 𝑒𝑒𝑐𝑐 may be proportional to circulating losses, especially in larger cables, so 𝜆𝜆′′ 1 should not be neglected. If so, better results are obtained (Fig.…”
Section: A Unarmored Cablessupporting
confidence: 88%
“…Another point of controversy is found in the bibliography regarding the source of the induced losses in the sheaths. Some studies [6,7,33,34] suggest that eddy-current losses may be proportional to circulating-current losses for large cables, so they should not be ignored in the computation of the SB-case sheath losses. However, there is no expression in [5] especially designed for evaluating eddy losses in this type of cable (Equation ( 7) is in fact only valid for SP single-core cables).…”
Section: Traditional Approach To Losses Estimation In Tcacsmentioning
confidence: 99%
“…As mentioned before, there is a controversial point regarding loss allocation in the sheaths, since [5] assumes that eddy losses may be neglected when sheaths are in SB, although some studies suggest the opposite for large cables [6,7,33,34]. Therefore, to clarify this point it is required to find a way to evaluate these terms separately, especially in TCACs.…”
Section: Separation Of Circulating and Eddy Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…For these single-core cables, to limit the circulating current on the metal outer sheath of the cable under normal operation, the metal outer sheath of the cable is generally grounded at a single end or cross-connected. Song- Wang et al (2018) and Chatzipetros and Pilgrim (2020) analyze common cable faults and divide them into the following six types: harsh environment, man-made damage, factory defects, nonstandard operation or untimely maintenance, and equipment aging (Zhang et al, 2021). The statistical data of cable fault current provided in Li et al (2019a) show that a large number of cable faults would lead to excessive sheath current, resulting in insulation damage of cable sheath and insulation breakdown between cable sheaths.…”
Section: Introductionmentioning
confidence: 99%